2021
DOI: 10.1101/2021.09.08.21263253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Provisional research criteria for the behavioral variant of Alzheimer’s disease A systematic review and meta-analysis

Abstract: Importance: The behavioral variant of Alzheimer disease (bvAD) is characterized by early and predominant behavioral deficits caused by AD pathology. This AD phenotype is insufficiently understood and lacks standardized clinical criteria, limiting reliability and reproducibility of diagnosis and scientific reporting. Objective: To perform a systematic review and meta-analysis of the bvAD literature, and use the outcomes to propose provisional research criteria for this syndrome. Data sources: A systematic liter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Future studies with more follow-up will help to further elucidate patterns of clinical progression in atypical AD. Other atypical variants of AD, including the dysexecutive 49 and behavioral 50 variants of AD, have now been recognized, and it will be important to determine whether our findings generalize to these other variants. Previous studies have shown that clinical disease progression differs between both LPA and PCA and the typical amnestic variant of AD, 41,51 but a cohort of typical AD with these same clinical tests is not available to include in this study.…”
Section: Discussionmentioning
confidence: 96%
“…Future studies with more follow-up will help to further elucidate patterns of clinical progression in atypical AD. Other atypical variants of AD, including the dysexecutive 49 and behavioral 50 variants of AD, have now been recognized, and it will be important to determine whether our findings generalize to these other variants. Previous studies have shown that clinical disease progression differs between both LPA and PCA and the typical amnestic variant of AD, 41,51 but a cohort of typical AD with these same clinical tests is not available to include in this study.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, our results suggest that specific social cognition tests and biometrics may be valuable in the clinical diagnosis of bvAD, such as the Ekman 60 faces test, Interpersonal Reactivity Index and Social Norms Questionnaire and eye movement patterns. The introduction of the first set of research criteria for bvAD [16] may greatly improve the general recognition of bvAD and the addition of the aforementioned tools may increase the diagnostic accuracy of bvAD even further in the future.…”
Section: Discussionmentioning
confidence: 99%
“…All bvAD cases fulfilled >2/6 core clinical criteria for bvFTD [18] in combination with amyloid-beta positivity based on CSF or PET examinations (see Table S1). According to recently proposed research criteria, all bvAD cases met criteria for at least "possible bvAD" (i.e., clinical bvAD in combination with positive amyloid-beta biomarkers [3], see table S1 for an overview of bvFTD symptoms in bvAD cases). In the same period, we consecutively included patients with "typical AD" (defined as amyloid-beta positive patients with MCI or AD dementia with an amnestic-predominant presentation) and patients with probable bvFTD according to the Rascovsky criteria [18] and with a negative amyloid status.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations